Case report: A fatal case of aortic and mitral valve endocarditis caused by Streptobacillus moniliformis - Winther, Mette (Eur Heart J Case Rep, 2020)
BACKGROUND: Infective endocarditis (IE) secondary to rat-bite fever (RBF) is rare but potentially lethal. Rapid diagnosis is of utmost prognostic importance. However, the diagnosis of RBF is challenging because Streptobacillus moniliformis does not grow under conventional culture conditions. CASE SUMMARY: A 65-year-old male without previous cardiac history presented with sudden onset of balance problems and facial palsy. For 2 weeks, he had experienced intermittent fever and myalgia. Transoesophageal echocardiography (TOE) revealed severe mitral and aortic valve IE with aortic root abscess. The patient underwent a double biological valve replacement. Blood cultures remained negative after 9 days of incubation. However, sub-cultivation on solid media demonstrated the growth of pleomorphic Gram-negative rods, identified as S. moniliformis. After 4 weeks of antibiotic therapy, he was discharged. One month later, control TOE showed valve excrescences and aortic annular aneurysm. Despite comprehensive surgery, antibiotic treatment, and intensive care, the patient died 1 week after reoperation. DISCUSSION: A fatal outcome of S. moniliformis IE is rare. The majority of previous cases describe underlying valvular abnormalities or death due to insufficient antimicrobial therapy. Here, the patient had no prehistory of valvular heart disease and despite appropriate antibiotics, the outcome was fatal. Rapid diagnosis of RBF IE has prognostic implications. Identification of S. moniliformis is, however, difficult, because the bacterium is fastidious and does not grow under standard laboratory conditions. Therefore, diagnosis often relies on clinical symptoms or a history of rodent exposure. Close attention to this disease by clinicians, in addition to, dialogue with clinical microbiologists is essential.